Holding Power of Orthopaedic Screws in Metacarpal and Metatarsal Bones of Young Calves - Kirpensteijn, J.; Jean, G.; Roush, J. K.; DeBowes, R. M.; Gaughan, E. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
The holding power and holding power per mm bone width of 4.5 mm and 5.5 mm cortical and 6.5 mm cancellous orthopaedic screws were obtained by tensile load-to-failure studies in excised metacarpal and metatarsal bones of young female Holstein calves. Holding power and holding power per mm bone width of 6.5 mm orthopaedic screws were significantly greater than those of 4.5 and 5.5 mm orthopaedic screws in the diaphysis and metaphysis. Significant differences were not detected between holding power and holding power per mm bone width of 4.5 and 5.5 mm orthopaedic screws. The holding power was not different between metacarpi and metatarsi. The limiting factor in all tests of holding power was the shear strength of the bone. We found that 6.5 mm orthopaedic screws have the greatest holding power in the metacarpal and metatarsal bones of young calves.This study compares the holding power of 4.5 mm and 5.5 mm cortical and 6.5 mm cancellous orthopaedic screws in excised metacarpal and metatarsal bones from young female Holstein calves. We found that 6.5 mm orthopaedic screws have the greatest holding power.
Keywords: Holding power; orthopaedic screws; calf; bone